If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -6x + 32 Reorder the terms: y = 32 + -6x Solving y = 32 + -6x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 32 + -6x
| 3x-5+2x+1=21 | | 1x-4=-5x-28 | | 3(7-5p)=0 | | 5(3x+2)=-15 | | 3x-5/2=-8 | | 0=t^2-3t^2-4t | | 4/7x7/11 | | -30=-9n+5n | | -30=-9n | | y=5x^2-4x | | 6(5v-8)=-25-4v | | 4(5+9f)=-34 | | 5x/6-2x-1/3=4/5 | | 4(n-3)+5n+8= | | 9(7c-6)=17-3c | | x-1/7=20/7 | | 9y-7y=32 | | (4z-5)(9+z)=0 | | -6=-5+h | | 5-4y=7 | | 7x+5x-20=80-8x | | 35=-5b | | 3*abs(x-2)=10 | | (56-98-12)*(5*22)= | | -13=d+5 | | -1*(-2)=1 | | 26-3a=-4(9a-5) | | -7=4+c | | 4b+15-6b-9=8-20 | | 3v+9-5=-31 | | (x-1)+(x-1)=3x-7 | | -7-5(1+9k)=30 |